2008
DOI: 10.1021/jp800351z
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene on Nitrogen-Adsorbed Cu(001) Nanopatterned Surfaces: From Preferential Nucleation to Layer-by-Layer Growth

Abstract: Nitrogen (N)-adsorbed Cu(001)-c(2 × 2) nanopatterned surfaces are used as templates to guide the growth of low-dimensional C 60 molecular nanostructures. At room temperature and during the initial stages of growth, C 60 molecules preferentially adsorb on the bare Cu regions on a partially N-covered grid surface. Subsequently, a two-dimensional molecular nanomesh is formed at low (∼0.28 monatomic layer) C 60 coverages. Further deposition leads to C 60 growth on the c(2 × 2)-N surface until the first molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
(129 reference statements)
0
9
0
Order By: Relevance
“…There are parallels with other systems where molecules or clusters are adsorbed at sites on an ordered array of local potential wells arising from self‐organization due to, for example, surface reconstruction or dislocation arrays,2729 including those adsorbed on boron nitride15 and graphene monolayers 6. However a distinguishing feature of our work is the observation that the trapping potential is sufficiently compliant to allow the molecules to relax and adopt a local configuration which is controlled by interactions with molecules trapped in neighboring energy minima so that extended, connected structures may be formed.…”
Section: Calculated Binding Energies Intermolecular Separations D Anmentioning
confidence: 99%
“…There are parallels with other systems where molecules or clusters are adsorbed at sites on an ordered array of local potential wells arising from self‐organization due to, for example, surface reconstruction or dislocation arrays,2729 including those adsorbed on boron nitride15 and graphene monolayers 6. However a distinguishing feature of our work is the observation that the trapping potential is sufficiently compliant to allow the molecules to relax and adopt a local configuration which is controlled by interactions with molecules trapped in neighboring energy minima so that extended, connected structures may be formed.…”
Section: Calculated Binding Energies Intermolecular Separations D Anmentioning
confidence: 99%
“…41 There are two main approaches to device fabrication from organic semiconductors: they can be based on either polymers or small molecules, 42 or sometimes a combination of the two materials types. 43,44 Of these systems, STM is best-suited to probing the characteristics of small molecule films, 45 with ultrahigh vacuum or ambient STM proving useful for vacuumdeposited organic semiconductor thin films, [46][47][48] and solution/ solid STM providing a direct view into the assembly and dynamics that occur in the formation of solution-processed films. In devicerelevant films, which are typically of the order of tens to hundreds of nanometres thick, the bottom film interface is buried and can be difficult to characterize, yet solution/solid STM directly visualises the molecular structure at the interface and can be combined with other techniques to understand how the interface structure affects the overall film morphology.…”
Section: Insight Into Architectures For Smallmolecule Organic Electromentioning
confidence: 99%
“…Moreover, high temperature difference between the filaments and substrate can intensify the diffusion of chemical radicals toward the substrate and thus enhance the nanomaterial growth rate [20]; our experiments have also demonstrated that indeed, the HFCVD technique is quite efficient in synthesizing the hybrid CNFs containing nanomaterials [6,19]. In particular, CH 4 was directly supplied to the CVD chamber without other carrier gas to ensure the fast absorption of CH 4 on the Au/carbon NP, because it benefits the layer-by-layer growth [21]. Furthermore, it was found that the oriented CNFs were grown in HFCVD system which differs from the plasma-enhanced CVD (PECVD) system.…”
Section: Introductionmentioning
confidence: 74%